Peran Motivasi Kerja Sebagai Pemediasi Antara Stres Kerja Dengan Kepuasan Kerja Pada Karyawan Brew Me Tea - Bayu Putra, Ngakan Catur; Supartha, Wayan Gede (Universitas Pahlawan Tuanku Tambusai, 2024)
Job satisfaction has an important role in supporting the success that the company wants to achieve. Job satisfaction can basically reflect the degree to which an employee likes his job. The need for mutual understanding efforts so that job satisfaction can be achieved is how the company understands the needs and expectations of its employees and how employees understand the common goals to be achieved between themselves and the company. The purpose of this study was to analyze the effect of work stress on job satisfaction with work motivation as a mediator in a tea production company. This study was conducted at the Brew Me Tea Company, the number of samples in this study was 60 people using saturated sampling. Data collection is carried out by conducting interviews and distributing questionnaires to company employees. This study used data analysis techniques with SPSS, namely path analysis. Based on the results of this research analysis shows that work stress has a negative and significant effect on job satisfaction, work motivation has a positive and significant effect on job satisfaction, work stress has a negative and significant effect on work motivation, and work motivation mediates the effect of job stress on job satisfaction. Based on these results, the management of Brew Me Tea is advised to increase the job satisfaction of its employees by paying attention to problems in work stress and work motivation of employees.